Application of Cymbopogon winterianus Jowitt and Azadirachta indica A. Juss in the control of Rhipicephalus (Boophilus) microplus - Peixoto, Erika Cosendey Toledo de Mello; Figueiredo, Amanda; Novo, Sylvia Marquart Fontes; Porto, Emília Paiva [UNESP]; Valadares, Fillipi [UNESP]; Silva, Luciana Pereira [UNESP]; Silva, Regildo Márcio Gonçalves da [UNESP] (My University, 2013)
Parasitism constitutes one of the main problems that affect livestock. Commercial acaricides have been used to control tick, but these chemicals have been responsible for the development of drug resistance and residues in the environment. Changes in the concept of production determined the search for natural measures, which guarantees animal sanity along with safety of the produced food. This assay had as objective to evaluate the citronella oil and neem oil in the control of bovine ticks. By the technique of adult ticks immersion, 280 ticks were evaluated, distributed in equal number throughout four treatments: negative control group, positive control (ivermectin), neem oil and citronella oil. It was analyzed the mortality index, estimated reproduction, product efficiency, index of eggs production and the hatchability rate. The efficiency of the product was verified by the mortality index just for the positive control group (100%) and citronella oil (97.14%). Also, the citronella oil inhibited the eclosion of eggs in 100%. The other treatments did not presented the minimum eclosion inhibition level of 95%. Under the conditions of the present assay citronella oil was efficient against Rhipicephalus (Boophilus) microplus. This result was not observed in relation to the neem oil.
Keywords: Agroecology; Citronella; Neem; Organic Production; Phytotherapy; Ticks